Pathyavihara and Yoga for Psychological Etiological Factors inInfertility - Khyati (International Research Journal of Ayurveda & Yoga, 2024)
Background: Infertility or Vandhyatva is a common problem among couples in the current scenario which can be due to various factors one of them being the psychological factor. Advancing technologies, changing lifestyles, stressful work patterns, lack of health awareness emotional instability in relationships, etc. can be the cause of infertility too. Observance of right Dinacharya Ritucharya Sadavritta and Yoga modalities can help in reducing these issues. Aim: The study aimed to understand the role of Pathyavihara and Yoga modalities in the reduction of psychological factors causing infertility. Methodology: It is literary research, Ayurveda classical texts, books, journals, and articles have been analyzed for this paper. Results: Imbalance in thoughts, emotions, etc. can be the triggering factors for stress, anxiety, and depression leading to a lack of acceptance in relations which can be the reason for infertility in any of the partners. This can be managed by the proper observance of Sadvritta, Dinacharya, Ritucharya Yoga, and Pranayama in daily life. Discussion: Infertility due to psychological factors can be originated in both males and females. These factors need to be addressed for a completely healthy progeny. Infertility or Vandhyatva is a disease of the male or female reproductive system defined by the failure to achieve a pregnancy after 12 months or more of regular unprotected sexual intercourse.[1] It is a common problem among couples which can be due to various reasons. The psychological factor is one among such factor. Advancing technologies, changing lifestyles, stressful work patterns, lack of health awareness emotional instability in relationships, etc. can be the cause of infertility too. This manuscript prioritizes the need for observance of right Dinacharya Ritucharya Sadavritta and Yoga modalities which can help in reducing these issues by managing the stress factors and relaxing mind and body along with enhancing the feeling of acceptance